2017
DOI: 10.1021/acs.jpcc.7b04199
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ga on H Reactivity with Ga-Stabilized δ-Pu Alloys

Abstract: The influence of Ga on the adsorption and solubility of H on Ga-stabilized δ-Pu alloys is investigated using density functional theory and experimentally via a Sieverts' apparatus. Allelectron DFT calculations, with spin−orbit coupling and full relaxations of the surface, are implemented to calculate H adsorption on δ-Pu−Ga alloy (111) surfaces. Chemisorption energies indicate that H prefers a 3-fold hollow site that binds strongly to a Pu-rich environment regardless of Ga concentration of the surface. Sites t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In general, our simulations overpredict the hydrogen saturation of δ-Pu by a factor of 3–6 compared to experimental values. It is unclear whether the lack of gallium in our simulations contributes to or minimizes this discrepancy, as a recent report found that Pu–Ga alloys absorb hydrogen less exothermically than unalloyed Pu in contrast to earlier reports, which found that Pu–Ga have higher hydrogen solubility limits than Pu. , Alternatively, this discrepancy could be a consequence of our decision to limit H–H interactions in our model to nearest neighbor O sites. The binding of a H in one O site effectively blocks the 12 neighboring O sites from being occupied because of the high energy required to insert a hydrogen in these locations.…”
Section: Resultsmentioning
confidence: 73%
“…In general, our simulations overpredict the hydrogen saturation of δ-Pu by a factor of 3–6 compared to experimental values. It is unclear whether the lack of gallium in our simulations contributes to or minimizes this discrepancy, as a recent report found that Pu–Ga alloys absorb hydrogen less exothermically than unalloyed Pu in contrast to earlier reports, which found that Pu–Ga have higher hydrogen solubility limits than Pu. , Alternatively, this discrepancy could be a consequence of our decision to limit H–H interactions in our model to nearest neighbor O sites. The binding of a H in one O site effectively blocks the 12 neighboring O sites from being occupied because of the high energy required to insert a hydrogen in these locations.…”
Section: Resultsmentioning
confidence: 73%
“…While there are some structural distortions due to the mono-vacancy, such as a monoclinic or tetragonal distortion, the electronic effects indicate a complex balance between the Pu 5f and 6d states. Due to the strong coupling of the Pu 5f and 6d states [50][51][52][53], in order for the Ga to stabilize the fcc matrix, hybridization of the Ga 4p and Pu 6d states must occur. With the introduction of a mono-vacancy, 5f-6d states decouple, thus intensifying the 5f states near the Fermi energy and broadening the 6d states, enabling hybridization with the Ga 4p states.…”
Section: Discussionmentioning
confidence: 99%
“…Previous DFT studies of adsorption of a single H atom or H 2 molecule on clean (100) and (111) surfaces of δ-Pu have all been conducted at low coverage conditions. [3][4][5][6][11][12][13] High surface coverage will be expected when P H 2 P eq H 2 . The equilibrium pressure P eq H 2 at room temperature, has not been experimentally verified but was recently predicted from simulations to be O(10 −19 ) bar.…”
Section: Introductionmentioning
confidence: 99%